The Perception and Interest of Career Choices in Agriculture: Case of Agroecotechnology and Agribusiness Students - Prasetyaningrum, Dian Islami; Ruminar, Hafida; Irwandi, Putra (HABITAT, 2022)
The agricultural sector contributes almost half of the Indonesian economy. Based on data from BPS in 2019-2020, this sector provides food for more than 270 million people and dominates the source of income in Indonesia by 33.4 million (27.33%). Unfortunately, the high opportunity and prospects are accompanied by a lack of enthusiasm among the younger generation to pursue agricultural careers, resulting in a decline in regeneration. Some influential factors included: (1) the perception that the agricultural sector is less promising in the future, (2) the lack of prestige of relatively low salaries, and (3) the existence and influence of social strata in the community. The current study aimed to investigate students' perceptions and interests, particularly those of agricultural students, concerning their career choices and corroborate the phenomena of the young generation's falling interest in agricultural careers. The participants were 100 agriculture students from the Faculty of Agriculture, Universitas Brawijaya (FP UB). The study implemented a quantitative approach with a survey method. The data were analyzed using Tableau. The results showed that there were two dominant factors, external and internal, that influenced the career choices of agriculture students. Additionally, the responses from the students based on gender (male and female) were also different. The findings of this study provide a broader view on how to improve students' interest in agricultural careers through external and internal assistance, namely motivation and practical experiences during the academic year.